Kinetic Features of Rearrangement of 3-Hydroxy-3-phenyl-indan-1,2-dione into 2,3- Epoxy-2-hydroxy-1-indanone in Acetonitrile in Dark - Tomar, Jyoti; Bansal, Manisha (Chemical and Materials Sciences: Developments and Innovations Vol. 8, 2024)
3-hydroxy-3-phenyl-indan-1,2-dione (dione) in acetonitrile (ACN) is converting back into 2,3-epoxy-2-hydroxy-1-indanone (epoxide) in dark. This is another equally significant observation after the detection of epoxide as the primary product in the photochemical reactions of 3-hydroxy-2-phenyl-4H-chromen-4-one (3HF) in ACN. A well-purified and characterized sample of dione has been taken for these studies. The electronic absorption spectrum of dione in ACN is changing continuously and kinetically in dark. This observation has been studied at 22±1 °C in detail. Concentration and spectra of both dione and epoxide at different times were obtained from their mixture after working out the absorption coefficients for the pure components at different wavelengths. From this data kinetic features of this reaction have been examined. Considering dione and epoxide to be in equilibrium, an equation has been derived that shows the linear dependence on a factor of concentration of dione vs time and also for concentration of epoxide vs time. The linear plots confirm the reversibility of the reaction. It can also be said that both the forward and backward reactions are first order since the derived equations are based on this assumption. It was also observed that this reaction is temperature-dependent as expected. Reaction has been studied at 14±1 and 32±1 °C also and from this data, rate constants for the forward and backward reactions were obtained. From the plots of lnk1 and lnk2 vs T activation energies, come out to be 72.175 kJmol-1 and 71.824 kJmol-1 for the conversion of dione into epoxide and from epoxide to dione.